Breast cancer relatives' physical activity intervention needs and preferences: qualitative results - Sheri J. Hartman; Rochelle K. Rosen (BMC, 2017)
Abstract Background While many risk factors for breast cancer, such as family history, are not modifiable, some, however, can be modified. The study used formative qualitative research to learn about the physical activity intervention preferences and needs of first-degree female relatives (FDFRs) of breast cancer patients; that information was then used to develop a targeted physical activity intervention. Methods Twenty FDFRs first completed a 12-week physical activity intervention and then attended two sequential focus groups (7 groups total). In the first set of focus groups participants provided feedback on the intervention. In the follow-up focus groups, proposed changes based on collected responses from the first groups were presented and participants provided feedback to further refine the intervention. Results Overall, we found strong interest for an intervention using breast cancer-related health concerns to promote positive behavior change. A theme underlying all of the feedback was the desire for a personalized intervention that was directly relevant to their lives. Participants wanted this personalization achieved through individually tailored content and incorporation of stories from other FDFRs. In order to successfully use concerns about breast cancer to motivate behavior change, participants also wanted a discussion about their individual risk factors for breast cancer including, but not limited to, lack of physical activity. Conclusions This study demonstrates women's interest in receiving personalized information and highlights specific ways to individualize an intervention that increases motivation and engagement. Using a sequential qualitative approach was effective for formative intervention development. Trial registration number NCT03115658 (Retrospectively registered 4/13/17).